The effects of a 10-day taper on repeated-sprint performance in females - Bishop, D.; Edge, J. (Journal of Science and Medicine in Sport, 2005)
While taper is a well-established practice in most endurance sports, no study has investigated the effects of taper on repeated-sprint ability (RSA). Eleven female, recreational, team-sport athletes (mean+/-SD: age = 19+/-3 y, VO2max = 39.0+/-6.4 mLxkg(-1)xmin(-1)) trained intensively three times per week for six weeks. Each week (on a non-training day), subjects performed a RSA test (5 x 6-s sprints every 30 s). Following the training period, subjects were given a 10-day exponential taper followed by a final RSA test. Following the taper, there was a non-significant increase in both total work (4.4% increase; P = 0.16) and peak power (3.2% increase; P = 0.18) during the 5 x 6-s test. There was however a significant decrease in work decrement (Wk 6: 10.2+/-3.5% v Wk 8: 7.9+/-4.3%; P< 0.05) following the 10-day taper. This is the first study to report the effects of taper on repeated-sprint performance. While not significant, the 10-day taper did result in a 3%-4% improvement in performance. Similar percentage improvements have been reported in swimmers and runners following seven to 14-day tapers. Further research is required to structure the optimal taper to improve repeated-sprint performance.